APPROACHES TO THE CHOICE OF METHOD FOR THE RESTORATION OF ABUTMENT TEETH IN PROSTHETICS WITH PARTIAL REMOVABLE DENTURES - Atahanov Alisher Vohobjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Complete edentulism is a worldwide, widespread problem and is the predominant diagnosis in patients over 65 years of age. Complete loss of teeth has a significant impact on the physiological and social parameters of human life, so this problem requires the closest attention. Orthopedic treatment with traditional full dentures is not an ideal treatment for complete edentulous, due to some of the difficulties that arise when using them. The study of this issue led to the introduction of intraosseous dental implants into the practice of orthopedic dentistry. The advantages of this technique are: a significant improvement in function, prevention of bone resorption, a significant increase in patient satisfaction with treatment.